Foule et public - Emmanuel Plasseraud (Conserveries Mémorielles : Revue Transdisciplinaire de Jeunes Chercheurs, 2012)
The film reception idea of French theory, in the silent period, is basically linked to the notion of crowd. This notion appeared during the19th century. It had many interpretations, which we can find again in cinema writtings. For those who fight against cinema, crowd can be seen as Gustave Le Bon describes it in its popularization of crowd psychology. Therefore, movie theaters are places where crowds relieve or excite their instincts. On the contrary, for film enthusiasts, cinema proposes a modern communal refoundation where crowds find back their lost spirituality. For them, theaters are places where an hypnotic phenomenon occurs, leading crowds. This conception is the foundation of the idea of « seventh art » invented by Canudo and used also, with diverses meanings, by Delluc, Gance, Epstein or L’Herbier. Is this conception suitable to the reality of the spectators practice at that time? Is it possible to consider the cinema audience as a whole, as it seems if we use the idea of crowd? We can answer no, and we can think that the gap between theory and reality of the film reception is one of the reasons explaining the problems of French cinema facing American cinema. The theorical deadlock of the French conception of film reception, due to the use of the notion of crowd, appears clearly in Germaine Dulac’s writtings. She was the first among French theoricians to doubt about the ability of cinema to get the crowds receiving Holy Communion. She understood that the audience, in its diversity, would dictate its tastes to the film-makers, expressing an idea that Hollywood producers had already assimilated.